2022
DOI: 10.3390/ijms23158402
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin (NRPs) Related Pathological Conditions and Their Modulators

Abstract: Neuropilin 1 (NRP1) represents one of the two homologous neuropilins (NRP, splice variants of neuropilin 2 are the other) found in all vertebrates. It forms a transmembrane glycoprotein distributed in many human body tissues as a (co)receptor for a variety of different ligands. In addition to its physiological role, it is also associated with various pathological conditions. Recently, NRP1 has been discovered as a coreceptor for the SARS-CoV-2 viral entry, along with ACE2, and has thus become one of the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 200 publications
0
17
0
Order By: Relevance
“…5E, F ). A previous study reported that NRP1 can act as a co-receptor of multiple tyrosine kinase receptors to promote tumor proliferation and migration [ 27 ]. Thus, it can be speculated that NRP1 may interact with EGFR and modulate EGFR phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…5E, F ). A previous study reported that NRP1 can act as a co-receptor of multiple tyrosine kinase receptors to promote tumor proliferation and migration [ 27 ]. Thus, it can be speculated that NRP1 may interact with EGFR and modulate EGFR phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…They act as co-receptors for proteins such as vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), hepatocyte growth factor (HGF), and transforming growth factor β (TGF-β). 7,9 There are two NRPs (NRP1 and NRP2) encoded by different genes on independent chromosomes but with a common domain structure. 8,9 While both NRPs share some characteristics and ligands, they differ in their tissue distribution and modulated signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 There are two NRPs (NRP1 and NRP2) encoded by different genes on independent chromosomes but with a common domain structure. 8,9 While both NRPs share some characteristics and ligands, they differ in their tissue distribution and modulated signaling pathways. 8,10 Moreover, while NRP1 has been widely studied and characterized, fewer studies have focused on NRP2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations